Jedna, żadna i sto tysięcy. Włoszka jako medium - Katarzyna Woźniak (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2019)
The stake in a heated discussion on reviving tarantism in the Salentian culture by initiators and partcicipants of the project ‘The spider of a dancing god’ was the reinterpretation of the phenomenon itself: tarantism, which was perceived as a thing of the past and an embarrassing social problem, was to become artistically modified, namely isolated from life and displayed on stage. Rejecting tarantism as a folk practice and an attempt at representing it could also be interpreted as turning a blind eye to the problem of a woman’s position in society, without proposing anything in turn. Technological and social progress did not go hand in hand with the emancipation of an Italian woman. Luigi Piradnello in his drama, and Franka Rame in her monodrama captured this phenomenon brilliantly.